An Evaluation of Intelligibility Debate in Pakistan - Anjum, Rehana Yasmin (Advances in Social Sciences Research Journal, 2016)
The English language came to the subcontinent through the British who ruled it for more than 100 years in the 17th century. Now the people of Pakistan and India are sandwiched between a more formal, sophisticated and literal English Language of the British and informal and casual English Language of the Americans. English is a lingua Franca which is acknowledged as a store house of knowledge and window onto world. At the start of the 21st century, most applied linguists were familiar with the fact that English is now spoken by a considerably greater number of non-native speakers than the native speakers. This incipient change in the status of English as an International language has opened a new vista of debate, namely, the intelligibility debate. It is assumed that English as an International Language has attained such a niche that its ownership by some group or some nation cannot be accepted as an authority, as it is connecting people across the globe through its mutual intelligibility trait. Those who can use it proficiently and even have command over its idiomatic use, whatever accent they may have must be acknowledged. The idea of following RP has been challenged by linguists like Jennifer Jenkins, Barbra Sieldhofer, Jonna Przedlacka, Katerzyna, etc and defended by Peter Trudgill and others of his school insist on the importance of a standard accent to be followed. This school says that every language has its own peculiar patterns which should be maintained while acquiring it otherwise that particular language will lose its peculiar flavor and identity and would gradually be lost like many other languages which could not resist simplification campaigns and eventually lost their originality. The current study explores this issue in Pakistani academic and professional situation among Pakistani Language practitioners with a survey based on the views of students and teachers through a questionnaire. The results show that all groups are in favor of an eclectic approach as is approved by Jenkins in her LFC proposal to NNS of English worldwide to facilitate convenience and ease. This study will initiate debates about an alternative way to teach and learn English as lingua franca.